2006
DOI: 10.2188/jea.16.35
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Health Education Combining Hot Spa Bathing and Lifestyle Education in Middle-aged and Elderly Women: One-year Follow-up on Randomized Controlled Trial of Three- and Six-month Interventions

Abstract: BACKGROUND This study attempted to clarify the duration of effects of 3- and 6-month comprehensive health education programs based on hot spa bathing, lifestyle education and physical exercise for women at 1-year follow-up. METHODS We examined middle-aged and elderly women who were randomly divided into two groups and followed up them for one year. Spa programmers instructed subjects for one hour in lifestyle education and physical exercise and for one hour in a half ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Finally, those who received health education at the workplace had low depression scores. Health education has previously been found to reduce depression 33) . Our results also indicated that health education appears to have a positive influence on mental health.…”
Section: The Mental Health Status Of Chinese Workers Living In Japanmentioning
confidence: 99%
“…Finally, those who received health education at the workplace had low depression scores. Health education has previously been found to reduce depression 33) . Our results also indicated that health education appears to have a positive influence on mental health.…”
Section: The Mental Health Status Of Chinese Workers Living In Japanmentioning
confidence: 99%
“…Thus, balneotherapy might play some role in the prevention of atherosclerosis. Immersion in thermal water exerts a beneficial effect also in the case of chronic heart disease (Cider et al 2006;Schmid et al 2007), and it also influences favourably levels of HbA 1c (Kamioka et al 2006) and plasma lipids (Strauss-Blasche et al 2003), and has beneficial effects in the case of diabetes (Ohtsuka et al 1996). Radon baths enhance the production of alpha-ANP and insulin (Yamaoka et al 2004).…”
Section: Mechanism Of Atherosclerosismentioning
confidence: 99%
“… 7 , 8 In addition, recent reports have demonstrated that comprehensive health education, which includes lifestyle education and exercise in combination with spa bathing, has positive effects for middle-aged and elderly people. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%